1994
DOI: 10.2307/1941739
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Isotope Study on Seasonal Food Web Dynamics in a Eutrophic Lake

Abstract: Phytoplankton, zooplankton, benthic invertebrates, and pond smelt were collected in a eutrophic lake (Lake Suwa, Japan) from spring to autumn in 1986 and 1987. Their stable carbon and nitrogen isotope ratios were analyzed together with conventional examination of the gut contents of pond smelt. Temporal variations in isotope rations were similar among the organisms other than benthic animals. The @d15N values of diet for several animals in the pelagic food web were estimated, assuming a stepwise enrichment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(153 citation statements)
references
References 37 publications
(39 reference statements)
10
141
1
1
Order By: Relevance
“…This range was compatible with the δ 15 N observed for potential prey of estuarine and palustrine wetlands (Nadelhoffer and Fry 1994;Michener and Schell 1994), although this was not surprising given the wide and overlapping range of δ 15 N observed for prey in aquatic ecosystems. The dynamic nature of wetlands, which can vary spatially and temporally in δ 15 N (Yoshioka et al 1994;France 1995;Boon and Bunn 1994), requires additional habitat-specific knowledge to decipher the nitrogen isotope records embodied in feather keratin. It is not known whether the ecosystems in which adult wood storks foraged were similar in structure and δ 15 N content, but if this were the case then the ~3‰ difference between feathers from the inland colonies would predict distinct feeding patterns, with nestlings from Chew Mill subsisting primarily on upper trophic-level consumers (piscivorous fish) and nestlings from Blackwater being fed lower trophic-level consumers (crayfish).…”
Section: Nitrogen Isotopes In Feathers and Food Resourcesmentioning
confidence: 99%
“…This range was compatible with the δ 15 N observed for potential prey of estuarine and palustrine wetlands (Nadelhoffer and Fry 1994;Michener and Schell 1994), although this was not surprising given the wide and overlapping range of δ 15 N observed for prey in aquatic ecosystems. The dynamic nature of wetlands, which can vary spatially and temporally in δ 15 N (Yoshioka et al 1994;France 1995;Boon and Bunn 1994), requires additional habitat-specific knowledge to decipher the nitrogen isotope records embodied in feather keratin. It is not known whether the ecosystems in which adult wood storks foraged were similar in structure and δ 15 N content, but if this were the case then the ~3‰ difference between feathers from the inland colonies would predict distinct feeding patterns, with nestlings from Chew Mill subsisting primarily on upper trophic-level consumers (piscivorous fish) and nestlings from Blackwater being fed lower trophic-level consumers (crayfish).…”
Section: Nitrogen Isotopes In Feathers and Food Resourcesmentioning
confidence: 99%
“…Yoshioka (1991) also used stable isotope measurements to demonstrate that pond smelt depended on various prey items, but their main food source was zooplankton. As a planktivorous fish, the main food sources for pond smelt are zooplankton, but feeding behavior gradually changes with growth (Yoshioka and Wada 1994;Ibe et al 2011). In Lake Soyang, a large freshwater reservoir, Lee et al (unpublished data) showed that pond smelt (H. nipponensis) change feeding behavior with growth.…”
Section: Isotopic Differences In Pond Smelt In Brackish Lagoonsmentioning
confidence: 99%
“…only occur in Lake Hwajinpo, unlike in Lake Youngrang and Mae (Wonju Regional Environmental Office 2008). N-fixing algae often have lower d 15 N values ranging from about (2 to '2 (Gu and Alexander 1993;Yoshioka and Wada 1994;Vuorio et al 2006). Therefore, we expect that pond smelt d 15 N values will reflect phytoplankton d 15 N values in our study lagoons through food web relationships, even though pond smelt do not directly consume phytoplankton (Yoshioka 1991;Yoshioka and Wada 1994).…”
Section: Isotopic Differences In Pond Smelt In Brackish Lagoonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of carbon and nitrogen stable isotopes (d 13 C and d 15 N) has been increasingly applied in studies of aquatic food webs because of their capacity to reveal food assimilation, and thus actual energy transfer, rather than merely ingestion as indicated by gut-content analysis or feeding observations (e.g., Yoshioka et al 1994;Hall et al 2001;O'Reilly et al 2002;Mantel et al 2004;Li and Dudgeon 2008). Stable isotopes of samples preserved in formalin, ethanol, and formalin-ethanol (fixation in formalin followed by storage in ethanol) can yield trophic information that may allow investigation of temporal changes in food-web dynamics, especially where stored specimens from aquatic ecosystems subject to anthropogenic impacts are available (Vander Zanden et al 2003).…”
mentioning
confidence: 99%